Transcatolicidades: contribuições à sociodiversidade brasileira - Sant'Anna, Sílvio Luiz (2013)
Transcatolicidades addresses three phenomena that contribute to inclusive social diversity in Brazil: Belo Monte Community, in Bahia, organized under the leadership of Antônio Conselheiro, the Chapel of Nosso Senhor do Bonfim, in the city of Sorocaba / SP, founded by Nhô João de Camargo; and Santo Daime, that appeared in Acre and coded by Mestre Irineu. From them, we seek to demonstrate how people of the lower classes, in addition to the religious spectrum, potentiated themselves as leaders in thought and sophisticated strategies that transformed the religious symbology, combining elements from different traditions, in collaborative languages who gave and give meaning to our inclusive Brazilianness